Komunitas Marjinal Keturunan Indonesia di Malaysia: Dampak Keterbatasan Akses Pendidikan Tinggi - Zuraidah Mohd Amin (Badan Strategi Kebijakan Hukum, 2025)
Education is one of the crucial elements needed in order to create a better nation. However, in reality, access to education is not equally accessible to all children regardless of their background. Specifically, the case of children of Indonesian immigrants in Malaysia has been impacted, as the privilege of tertiary education has been limited since the implementation of the Malaysia's New Economic Policy in 1971. The children of Indonesian immigrants are born in Malaysia and granted Malaysian citizenship under certain terms and conditions but are not classified as a group of aboriginal people. This condition leads to the question of how far the limitation of education access impacts the long-term socio-economic status towards these children. Thus, this paper analyzed the impact on the socio-economic status of children of Indonesian immigrants in Malaysia by conducting in-depth interviews with ten informants who are facing a similar situation and who were selected from states with a high concentration of Indonesian immigrants to observe their significant impacts. Additionally, an in-deep analysis of the series of development policies introduced by the Malaysian government will be conducted in the discussion. The findings show that these limitations have a significant impact on their long-term socio-economic mobility. Furthermore, an analysis of Malaysia's development policies reveals that the ethnicity-based quota system remains a major obstacle to accessing tertiary education for this group. This paper contributes to a continuous debate on the rights of education, citizenship, and socio-economic changes among the children of Indonesian immigrants in Malaysia. More inclusive policies are needed to ensure fairer access to higher education.